Analysis of Risk Factors Associated with Hepatitis B and C Infection in Correctional Institutions in British Columbia - RG Préfontaine; RK Chaudhary; RG Mathias (Canadian Journal of Infectious Diseases)
The factors associated with infection with hepatitis B (hbv) and C viruses (hcv) were studied in residents of correctional institutions in British Columbia. Four hundred and fifteen residents volunteered to participate in this study. Among 415 residents tested, 28% were positive for hvb or hcv markers. Sixty-five per cent of the residents positive for hbv markers were also infected with hcv. However, in hbv-negative residents, only 14% were positive for antibody to hcv (anti-hcv). The highest rates for hbv and hcv were in 25- to 44-year-old residents. The analysis of risk factors and infection predictors in 354 residents showed that intravenous drug use and history of hepatitis were associated with infection with both hbv and hcv. The relative risk for hbv in intravenous drug users was 4.4 times that in nonusers; for hcv relative risk was 3.4 times. In the group with history of hepatitis, the relative risk was 6.2 and 4.5 times for hbv and hcv, respectively. The multivariate analysis of the data showed that both intravenous drug use and a history of hepatitis were significant (P<0.0001). Tattooing or history of transfusion was not associated with increased risk for hcv, but tattooing and age were significant factors for hbv.